2013
DOI: 10.3233/prm-130244
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Actical and Actiheart monitor in ambulatory children with Spina Bifida

Abstract: BACKGROUND: Ambulatory children with Spina Bifida (SB) often show a decline in physical activity leading to deconditioning and functional decline. Therefore, assessment and promotion of physical activity is important. Because energy expenditure during activities is higher in these children, the use of existing pediatric equations to predict physical activity energy expenditure (PAEE) may not be valid. AIMS: (1) To evaluate criterion validity of existing predictions converting accelerocounts into PAEE in ambula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The Actiheart (Camntech), will be used to detect the intensity of physical activity (Brage et al 2005 ). The Actiheart is a small device detecting the heart rate frequency via two electrode-stickers on the chest and has been used previously in children with Spina Bifida (De Groot et al 2013 ). During the 1 week of wearing the activity monitor, the participant will also fill out an activity diary in order to interpret missing data of the activity monitor.…”
Section: Designmentioning
confidence: 99%
“…The Actiheart (Camntech), will be used to detect the intensity of physical activity (Brage et al 2005 ). The Actiheart is a small device detecting the heart rate frequency via two electrode-stickers on the chest and has been used previously in children with Spina Bifida (De Groot et al 2013 ). During the 1 week of wearing the activity monitor, the participant will also fill out an activity diary in order to interpret missing data of the activity monitor.…”
Section: Designmentioning
confidence: 99%
“…35 Indeed, a study using the Actical, an accelerometer also worn at the hip, in adolescents with spina bifida showed poor validity in predicting energy expenditure. 23 The use of heart rate as determined by the Actiheart may be the preferred method to evaluate physical activity and sedentary behaviour. A former study evaluating the use of the Actiheart in adolescents with spina bifida found that use of heart rate was preferred over additional use of accelerometer counts, which did not add to the validity of the models predicting energy expenditure during sedentary and active behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A former study evaluating the use of the Actiheart in adolescents with spina bifida found that use of heart rate was preferred over additional use of accelerometer counts, which did not add to the validity of the models predicting energy expenditure during sedentary and active behaviour. 23 Furthermore, the Actiheart has been validated for use in children with various chronic diseases 36 and the Actiheart placement on the chest may allow appropriate measurement of heart rate in ambulatory and non-ambulatory adolescents. It should be noted that while the Actiheart measures a physiological response to activity, it is not measuring actual movement; heart rate measurement may be influenced by emotions and stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations